The Catastrophic State of Catastrophic Health Care Coverage. Hearing before the Special Committee on Aging. United States Senate, One Hundredth Congress, First Session (Birmingham, Alabama) - Congress of the U.S., Washington, DC. Senate Special Committee on Aging; Congress of the U.S., Washington, DC. Senate Special Committee on Aging ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
This document presents witnesses' testimonies and prepared statements from the Senate hearing held in Birmingham, Alabama to alert the public to the problems associated with catastrophic illness; learn what community services exist for older adults; and clarify what requirements for services, research, and education must be met to formulate an effective catastrophic health proposal. It includes statements by Senators Richard Shelby, Howell Heflin, and John Melcher. Witnesses providing testimony include: (1) William Bridgers, School of Public Health, University of Alabama at Birmingham; (2) Jim and Geraldine Turner, who present the caregiver perspective; (3) Kathy Fuller, who testifies on her family's experiences as victims and caregivers; (4) George Layton, Alabama State Legislative Committee, American Association of Retired Persons; (5) Raymond Walter, National Association of Retired Federal Employees; (6) Amelia Heath, FOCUS on Senior Citizens of Tuscaloosa County, Alabama; (7) Barbara Bonfield, Jefferson County Office of Senior Citizens Activities; (8) Allan Goldstein, Birmingham physician; (9) Beverly Friedlander, Saint Vincent's Hospital, Birmingham; (10) Karen Hermanson, Visiting Nurse Association; and (11) Joseph Bolen, Blue Cross and Blue Shield of Alabama. Materials related to the hearing are appended. (NB)
Availability: Superintendent of Documents, Congressional Sales Office, U.S. Government Printing Office, Washington, DC 20402.
ERIC Note: Serial No. 100-4.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Caregivers; Chronic Illness; Health Insurance; Health Needs; Hearings; Older Adults; Public Policy; Catastrophic Health Care; Alabama (Birmingham) -- Congress 100th; Legal/Legislative/Regulatory Materials